2004
DOI: 10.1111/j.1365-2036.2004.02277.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ablation of Barrett's oesophagus: a randomized‐controlled trial of photodynamic therapy vs. argon plasma coagulation

Abstract: SUMMARYBackground: Barrett's oesophagus is the major risk factor for oesophageal adenocarcinoma. 5-Aminlevulinic acid-induced photodynamic therapy and argon plasma coagulation have been shown to be effective for ablating Barrett's oesophagus, but a comparative trial of these two modalities has not been reported. Aims: To compare photodynamic therapy and argon plasma coagulation for the ablation of Barrett's oesophagus. Methods: A total of 68 patients (54 male, 14 female; median age 61) with Barrett's oesophagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 51 publications
1
81
0
7
Order By: Relevance
“…Today PDT is not only considered as palliative therapy but also as a treatment option for early lung cancer, actinic keratosis, and basal cell carcinoma. Currently, the use of PDT for disseminated tumors, localized disease and precancerous lesions is under investigation for intraperitoneal carcinomatosis [42,43], Barrett's oesophagus [59], bladder cancer [60], pituitary tumors [61], and glioblastoma [62]. As PDT becomes more widely used, the necessity of increasing specificity becomes important especially when treating tumors in complex anatomical sites such as in the peritoneal cavities.…”
Section: Discussionmentioning
confidence: 99%
“…Today PDT is not only considered as palliative therapy but also as a treatment option for early lung cancer, actinic keratosis, and basal cell carcinoma. Currently, the use of PDT for disseminated tumors, localized disease and precancerous lesions is under investigation for intraperitoneal carcinomatosis [42,43], Barrett's oesophagus [59], bladder cancer [60], pituitary tumors [61], and glioblastoma [62]. As PDT becomes more widely used, the necessity of increasing specificity becomes important especially when treating tumors in complex anatomical sites such as in the peritoneal cavities.…”
Section: Discussionmentioning
confidence: 99%
“…One popular strategy for treating BE and thus preventing its progression to esophageal adenocarcinoma is through endoscopic ablation using modalities such as multipolar electrocoagulation, photodynamic therapy, laser therapy, cryotherapy, mucosal resection, argon plasma coagulation, and radiofrequency ablation [7,8,9,10,11,12]. Ablation of BE combined with acid suppression by proton pump inhibitor therapy has been shown to achieve complete reepithelialization of the wounded areas with neosquamous epithelium (NSE) [11,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The reported rate of successful ablation of combined low grade dysplasia or Barrett's esophagus itself ranges from 82% to 100%, and successful ablation rate in high grade dysplasia or cancer was 77% to 91% (Table 3). 9,[12][13][14][15][16] However, these studies confirmed the feasibility, safety of the PDT, and obtained mixed success as well in terms tumor response. Some report complete histologic response in "advanced" tumors, whereas others report only partial response even in "early" tumors.…”
Section: Omp Alone 31%mentioning
confidence: 79%